2020
DOI: 10.1002/jbmr.4111
|View full text |Cite
|
Sign up to set email alerts
|

A Signature of Circulating miRNAs Associated With Fibrous Dysplasia of Bone: the mirDys Study

Abstract: Fibrous dysplasia (FD) is a rare bone disease caused by activating mutations of GNAS encoding the Gsα protein, enhancing cyclic adenosine monophosphate (cAMP) production by overstimulation of adenylyl cyclase and impairing osteoblastic differentiation. The clinical presentation ranges from asymptomatic to polyostotic forms with severe disability, explained by the mosaic distribution of the GNAS mutation. Physicians have to deal with the gap of knowledge in FD pathogenesis, the absence of prognostic markers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…In addition, a few of the bone-associated miRNAs, e.g., miR-150-5p, miR-223-3p, miR-93-5p have been detected in matrix particles or circulating exosomes ( Kelch et al, 2017 ; Legrand et al, 2020 ; Lu et al, 2019 ; Mäkitie et al, 2018 ; Perez-Sanchez et al, 2018 ; Hosokawa et al, 2017 ) and may therefore be important in cell-cell communication and systemic regulation of body functions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few of the bone-associated miRNAs, e.g., miR-150-5p, miR-223-3p, miR-93-5p have been detected in matrix particles or circulating exosomes ( Kelch et al, 2017 ; Legrand et al, 2020 ; Lu et al, 2019 ; Mäkitie et al, 2018 ; Perez-Sanchez et al, 2018 ; Hosokawa et al, 2017 ) and may therefore be important in cell-cell communication and systemic regulation of body functions.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have shown that miRNAs are involved in a series of biological processes, such as cell proliferation and differentiation. A recent report identified a number of circulating miRNAs that are potential negative regulators of gene expression in bone cell progenitors and were associated with FD (Legrand et al 2020 ). In this study, we performed miRNA sequencing analysis of normal BMSCs and FD BMSCs, and the results showed that miR-181a-5p, miR-145-3p, miR-98-3p and miR-92b-5p were significantly differentially expressed miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Bai et al, (28) Pan et al, (29) and Legrand et al (30) miR-6769b-5p À3.372 0.009 Overexpressed by bone marrow-derived macrophages leading to a phenotypic switch to fibrolytic macrophages with increased MMP9 expression and reduced ATF4 and inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Bai et al (24) , Pan et al (25) , and Legrand et al (26) miR-6769b-5p -3.372 0.009 Potentially, it is expression by bone marrow-derived macrophages. miR-351-5p -2.751 0.002 Yes, it is involved in the regulation of Dishevelled 2 (Dvl-2), a key mediator of the Wnt/β-catenin signaling pathway.…”
Section: Literature Evidencementioning
confidence: 99%